Proteomics signatures associated with hip arthropathy in ankylosing spondylitis - Wen, Xianghui; Fang, Linkai; Chen, Zena; Liu, Dong; Wen, Shenghui; Li, Jinwei; Li, Qiuxia; Wei, Qiujing; Cao, Shuangyan; Zhang, Peng; Gu, Jieruo (Frontiers in Medicine, 2025)
ObjectiveAnkylosing spondylitis (AS) is a chronic inflammatory disease primarily affecting the axial skeleton and peripheral joints, with hip arthropathy representing a severe complication that critically impairs mobility. While persistent inflammation is a hallmark of AS, the molecular mechanisms driving hip involvement remain poorly characterized. This study aimed to identify and validate protein biomarkers associated with hip arthropathy progression in AS through integrated proteomic and functional analyses.MethodsLiquid chromatography-mass spectrometry (LC–MS/MS) was employed to screen for differentially abundant proteins (DAPs) in hip joint tissues from 30 AS patients and 14 non-AS controls. Bioinformatics methods were utilized to screen for and identify key DAPs.ResultsA total of 2,050 proteins were relatively quantified, with 109 DAPs (34 upregulated and 75 downregulated) meeting the criteria of p < 0.05 and a fold change ≥1.5 or ≤0.67. Enriched GO terms represented by DAPs included the Wnt signaling pathway, MAPK cascade, and antigen processing and presentation of exogenous peptide antigen via MHC class I. The main Kyoto Encyclopedia of Genes and Genomes (KEGG) pathways included the PI3K-Akt signaling pathway, ribosome, metabolic pathways, and neutrophil extracellular trap formation. The protein–protein interaction (PPI) network identified ribosomal proteins (RPs), including RPS11, RPS24, RPL35, RPS3A, RPS6, RPS8, RPS14, and RPS7, as highly connected hub proteins. These RPs were significantly enriched in pathways associated with hip arthropathy pathogenesis, particularly osteoblast differentiation and T cell-mediated immune regulation.ConclusionBased on proteomics approaches and bioinformatics analysis, this study discovered DAPs and signaling pathways associated with hip arthropathy in AS. It may provide potential as screening tools or therapeutic targets for AS, warranting further research for validation.